From oncogenesis to prognosis: the roles of the immunoproteasome in cancer - Béland, Delphine; Viens, Mélissa; Kalin, Emma Mary; Bourgeois-Daigneault, Marie-Claude (Frontiers in Immunology, 2025)
The proteasome (prosome, macropain) is a key cellular organelle responsible primarily for protein homeostasis, by degrading damaged or misfolded proteins. Proteasome-processed protein fragments can then be further trimmed and funneled to the major histocompatibility complex class I (MHC-I) antigen presentation pathway for cell surface display and immune recognition. Various types of proteasomes can be found in mammalian cells with different expression patterns and cleavage abilities. As such, the immunoproteasome (ImP) preferentially cleaves proteins to yield MHC-I-compatible fragments. It is constitutively expressed by some immune cells and can be induced by pro-inflammatory signals. Interestingly, it was also found to be expressed in multiple types of cancers and proteasome activity can be modulated by some cancer therapies. A better understanding of its impact on cancer progression, prognosis and treatment response is therefore needed to guide treatment decisions. In this review, we focus on the multiple roles of the ImP in cancer, including its interplay with the immune system, as well as its impact on patient outcomes.